How much sustainability substance is in urban visions? – An analysis of visioning projects in urban planning. (November 2015) - John, Beatrice; Keeler, Lauren Withycombe; Wiek, Arnim; Lang, Daniel J.
Highlights: Sustainability is critical for urban development visions. No vision analyzed fully adopted sustainability. Instead, optimizing the built environment was the dominant goal. Lacking acknowledgement of regional embeddedness hinders holistic visions. Specific procedures can enhance sustainability substance of urban visions. Abstract: Cities are hubs of social interaction, trade, and innovation. Yet, they face sustainability challenges of economic decline, social injustices, and environmental degradation. Urban planning is a critical instrument to cope with these challenges. Visioning, the process of constructing desirable future states, can provide direction for sustainability-oriented planning and decision-making and is increasingly used in this capacity. However, there is ample evidence that urban visions are often not designed along a robust set of sustainability principles. We analyze nine explicitly sustainability-related urban visions from Sweden, Germany, Ireland, Canada, USA, and Australia with respect to their sustainability substance, i.e. in how far they, broadly and in detail, adhere to sustainability principles. Using rough set analysis, we identify a number of procedural components that enable or obstruct the inclusion of sustainability substance in urban visions. Results indicate that the sampled urban visions do not substantially and comprehensively include sustainability substance, instead narrowly focus on optimizing the built environment, for example. Furthermore, the sustainability substance of visioning processes benefits from stakeholder engagement that includes capacity building, whereas some other types of participation obstruct the inclusion of sustainability substance. The study concludes with recommendations for visioning processes to yield urban visions with sustainability substance inclusive of a diverse and integrated set of sustainability principles.